Factors Influencing the Utilization of Antenatal Care, Institutional Delivery, and Postnatal Care Services Among Women in Bangladesh - Akibul Islam Chowdhury; Mohammad Asadul Habib; Tanjina Rahman (Makara Journal of Health Research, 2022)
Background: In Bangladesh, the utilization of maternal health services is low, which triggers pregnancy-related complications and maternal deaths. The current community-based cross-sectional study aims to evaluate the factors associated with antenatal care (ANC), institutional delivery, and postnatal care (PNC) service utilization among women in selected areas of Southwest Dhaka, Bangladesh.